1987
DOI: 10.1111/j.2044-8309.1987.tb00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem and problem‐solving behaviour in close relationships

Abstract: Three studies examined the relationship between self‐esteem and responses to periodic decline in close relationships. A four‐category typology of responses to dissatisfaction was utilized: exit — actively destroying the relationship; voice — actively and constructively attempting to improve conditions; loyalty — passively but optimistically waiting for conditions to improve; and neglect — passively allowing the relationship to deteriorate. It was hypothesized that individuals with stronger self‐esteem would at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 0 publications
0
29
0
4
Order By: Relevance
“…Nor was it the case that those with an interdependent self-construal were more likely to report the passive, destructive, response of neglect (ignoring the relationship, passively allowing it to deteriorate). It is well-established that people in intact, satisfying romantic relationships are most likely to report the constructive responses to conflict (i.e., voice and loyalty; see e.g., Rusbult et al, 1986aRusbult et al, , 1986bRusbult et al, , 1982Rusbult, Morrow, & Johnson, 1987). Thus, our self-construal differences were most evident for the kinds of responses that our participants say they are most likely to use.…”
Section: Discussionmentioning
confidence: 41%
“…Nor was it the case that those with an interdependent self-construal were more likely to report the passive, destructive, response of neglect (ignoring the relationship, passively allowing it to deteriorate). It is well-established that people in intact, satisfying romantic relationships are most likely to report the constructive responses to conflict (i.e., voice and loyalty; see e.g., Rusbult et al, 1986aRusbult et al, , 1986bRusbult et al, , 1982Rusbult, Morrow, & Johnson, 1987). Thus, our self-construal differences were most evident for the kinds of responses that our participants say they are most likely to use.…”
Section: Discussionmentioning
confidence: 41%
“…Many studies have investigated the relationship among responses to relationship dissatisfaction and various variables such as gender role orientation (Rusbult, Zembrodt, & Iwaniszek, 1986) partner's perspective taking (Arriaga & Rusbult, 1998;Rusbult et al, 1991), empathic accuracy (Kilpatrick, Bissonnette, & Rusbult, 2002), trust to partner (Wieselquist et al, 1999), self-esteem (Kumashiro, Finkel, & Rusbult, 2002;Rusbult, Morrow, & Johnson, 1987), self-control (Finkel & Campbell, 2001), and attachment styles (Gaines & Henderson, 2002;Gaines et al, 1997 M a n u s c r i p t RESPONSES TO RELATIONSHIP PROBLEMS 5 et al, 2003;Tucker & Anders, 1999) have demonstrated that partners' perception of reactions to relational problems effect relationship satisfactions and relationship quality. Similarly, some studies conducted in Turkish culture (e.g., Taluy, 2013) have revealed that perceptions of couples about their partners' reactions to relational problems effect relationship satisfaction.…”
Section: Exit Voice Loyalty Neglect Responses To Dissatisfaction (mentioning
confidence: 97%
“…Possibly the reason for this is that high self-esteem leads to relationship problems, too. Rusbult, Morrow, and Johnson (1987) examined four types of responses to problems within close relationships, and found that self-esteem produced the largest difference in the active-destructive ("exit") category of responses. People with high self-esteem were significantly more likely than others to respond to problems and conflicts by deciding to leave the relationship, seeking other partners, and engaging in other behaviors that would actively contribute to the deterioration of the relationship.…”
Section: Romantic and Intimate Relationshipsmentioning
confidence: 99%